(untitled) (American Journal of Islam and Society, 1993)
Ate appearances deceiving? Do objects behave the way they do because God wills it? Ate objects impetmanent and do they only exist because they ate continuously created by God? According to a1 Ghazlli, the answers to all of these questions ate yes. Objects that appear to be permanent are not. Those relationships commonly tefemed to as causal are a result of God’s habits rather than because one event inevitably leads to another. God creates everything in the universe continuously; if He ceased to create it, it would no longer exist. These ideas seem oddly naive and unscientific to people living in the twentieth century. They seem at odds with the common conception of the physical world. Common sense says that the universe is made of teal objects that persist in time. Furthermore, the behavior of these objects is reasonable, logical, and predictable. The belief that the univetse is understandable via logic and reason harkens back to Newton’s mechanical view of the universe and has provided one of the basic underpinnings of science for centuries. Although most people believe that the world is accutately described by this sort of mechanical model, the appropriateness of such a model has been called into question by recent scientific advances, and in particular, by quantum theory. This theory implies that the physical world is actually very different from what a mechanical model would predit. Quantum theory seeks to explain the nature of physical entities and the way that they interact. It atose in the early part of the twentieth century in response to new scientific data that could not be incorporated successfully into the ptevailing mechanical view of the universe. Due largely ...